2022
DOI: 10.1001/jamanetworkopen.2022.46400
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Human Leukocyte Antigen DR Alleles, Immune-Related Adverse Events, and Survival Associated With Immune Checkpoint Inhibitor Use Among Patients With Advanced Malignant Melanoma

Abstract: ImportanceTreatment with immune checkpoint inhibitors (ICIs) has increased survival in patients with advanced malignant melanoma but can be associated with a wide range of immune-related adverse events (irAEs). The role of human leukocyte antigen (HLA)–DR alleles in conferring irAE risk has not been well studied.ObjectiveTo evaluate the association between irAEs and treatment response, survival, and the presence of HLA-DR alleles after ICI therapy in advanced melanoma.Design, Setting, and ParticipantsThis case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…In comparison with our previous study (5), the current study was conducted on a larger scale with confirmation of HLA-DPB1*05:01 predominance in ICI-T1DM than those of general controls and ICIcontrols with the same ethnic background. Current study may also support other reports describing that HLA-DR4 alleles are increased in patients with ICI-T1DM in the United States (21,22), although these studies are not at the detailed allelic levels. Based on the conditional multiple regression analysis, in addition to HLA-DPB1*05:01 allele, alleles of HLA-DRB1*04:05 and DQB1*04:01, and HLA-DRB1*04:05-DQB1*04:01 haplotype were found to be susceptible to ICI-T1DM (Tables 2A-E) .…”
Section: Discussionsupporting
confidence: 88%
“…In comparison with our previous study (5), the current study was conducted on a larger scale with confirmation of HLA-DPB1*05:01 predominance in ICI-T1DM than those of general controls and ICIcontrols with the same ethnic background. Current study may also support other reports describing that HLA-DR4 alleles are increased in patients with ICI-T1DM in the United States (21,22), although these studies are not at the detailed allelic levels. Based on the conditional multiple regression analysis, in addition to HLA-DPB1*05:01 allele, alleles of HLA-DRB1*04:05 and DQB1*04:01, and HLA-DRB1*04:05-DQB1*04:01 haplotype were found to be susceptible to ICI-T1DM (Tables 2A-E) .…”
Section: Discussionsupporting
confidence: 88%
“…According to recent studies, patients' human leukocyte antigen (HLA) expression may be predictive of their risk and severity of irAEs. Future studies should incorporate genomic test data to assess the association between HLA status and the development of irAE for older patients 53–55 . There is also a lack of data about irAE severity (e.g., Common Terminology Criteria for Adverse Events grading) in the SEER‐Medicare linked database.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should incorporate genomic test data to assess the association between HLA status and the development of irAE for older patients. 53 , 54 , 55 There is also a lack of data about irAE severity (e.g., Common Terminology Criteria for Adverse Events grading) in the SEER‐Medicare linked database. It is also necessary to conduct future studies to assess the incidence and risk factors associated with severe irAEs.…”
Section: Discussionmentioning
confidence: 99%
“…Examples include pruritus and atopic dermatitis, 73,74 colitis and inflammatory bowel diseases, 75 thyroiditis and Grave's disease, 76,77 and arthritis 78 . A summary of the HLA alleles associated with ICI‐induced irAEs identified by us and others and found in Table 1 79–87 . These findings will require larger genome‐wide association studies to confirm the identified associations.…”
Section: The Search For Biomarkers Associated With Ici‐induced Iraesmentioning
confidence: 90%
“…78 A summary of the HLA alleles associated with ICI-induced irAEs identified by us and others and found in Table 1. [79][80][81][82][83][84][85][86][87] These findings will require larger genome-wide association studies to confirm the identified associations.…”
Section: Hlas Associated With Increased Risk Of Developing Iraesmentioning
confidence: 99%